NON MEDICAL FACTORS THAT AFFECT USAGE OF LONG ACTING REVERSIBLE CONTRACEPTIVE (LARC) IN WOMEN AFTER CHILDBIRTH IN INDONESIA - Cindra Paskaria (Journal of Medicine and Health, 2015)
The Long Acting Reversible Contraceptive ( LARC) is a method of contraception that is effective and efficient to prevent pregnancy or limit births, but its use in Indonesia is still low especially in women after childbirth.  This may increase the risk of unwanted pregnancy and short birth interval.  The purpose of this research is to find out what factors affect the use of LARC in women after childbirth in Indonesia. This research is an analysis of secondary data Indonesia Demographic and Health Survey 2012, with stamp 3,918 Women’s Reproductive Age, which is between 15-49 years  old and  they had given birth one year before the survey.  The data were analyzed by using simple logistic regression analysis.  This research shows that the proportion of women who used LARC after childbirth in Indonesia in 2012 was 7.31% and it was influenced by the level of socio-economic, domiciles, the husband’s level of education, the number of children born alive, the number of children still living, the desired number of children, the role of husband, and the role of religious figures. Keywords: LARC, women after childbirth, non medical factors